2012
DOI: 10.1016/j.epsl.2011.12.022
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of impurities on the densification of polar firn

Abstract: Editor: P. DeMenocalKeywords: polar firn density densification impurity density variability Understanding polar firn densification is crucial for reconstructing the age of greenhouse gas concentrations extracted from ice cores, and for the interpretation of air in ice as a dating tool or as a climate proxy. Firn densification is generally modeled as a steady burial and sintering process of defined layers, where the structure of the layering is maintained along the whole firn and ice column. However, available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
153
2

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(167 citation statements)
references
References 41 publications
7
153
2
Order By: Relevance
“…It also focuses on differentiating polar sites, or relating microstructure to deformation mechanisms. However, despite giving useful information for densification modeling (e.g., Hörhold et al, 2011Hörhold et al, , 2012, these X-ray tomography studies do not provide an unambiguous prediction of LIZ and COD. To that end, the recent work of Schaller et al (2017) uses X-ray tomography to scan very large volumes of firn from three different polar sites.…”
Section: A Burr Et Al: X-ray Tomography Of Polar Firnmentioning
confidence: 99%
“…It also focuses on differentiating polar sites, or relating microstructure to deformation mechanisms. However, despite giving useful information for densification modeling (e.g., Hörhold et al, 2011Hörhold et al, , 2012, these X-ray tomography studies do not provide an unambiguous prediction of LIZ and COD. To that end, the recent work of Schaller et al (2017) uses X-ray tomography to scan very large volumes of firn from three different polar sites.…”
Section: A Burr Et Al: X-ray Tomography Of Polar Firnmentioning
confidence: 99%
“…The precise nature of this densification depends on a number of local factors that also vary temporally (Arthern et al, 2010), including surface density and stratification (Hörhold et al, 2011), surface mass balance and temperature (e.g., Herron and Langway, 1980), as well as dynamic recrystallization and the strain regime. Recent studies also highlight the role of microstructure (Gregory et al, 2014) and impurities (Hörhold et al, 2012;Freitag et al, 2013a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Implication for the local insolation modulation of gas transport conditions during bubble close-off Fujita and others (2009) hypothesized that the strength of the textual effects determines the duration for firn-to-ice transition and so determines the degree of lower O 2 /N 2 ratio and smaller TAC. More recently, based on the empirical correlations between Ca 2+ concentrations and densification enhancement, Hörhold and others (2012) suggested that seasonal density-layering loses its initial stratigraphic information in the top 10-15 m of the firn column, and therefore a direct line of influence of the local radiation balance on the surface snow density cannot be the ultimate reason for the observed O 2 /N 2 fractionation at close-off depth. In the present study, based on the data and the explanations, we hypothesize as follows: (1) density-layering does not lose its initial textural information in the shallow portion (10-15 m in the Hörhold and others (2012) cases and 0-30 m at DF) of the firn column, though some ions provide additional features to the initial density-layering.…”
mentioning
confidence: 99%